Stephanostomum tantabiddii n. sp. (Digenea: Acanthocolpidae) from Carangoides fulvoguttatus (Forsskal, 1775) (Perciformes: Carangidae) from Ningaloo Reef, Western Australia - Bray, Rodney A.; Cribb, Thomas H. (Zootaxa, 2004)
A new species, Stephanostomum tantabiddii n. sp., is described from the yellowspotted trevally Carangoides fulvoguttatus from Ningaloo Reef, Western Australia. It has 38 45 circum-oral spines and the vitellarium reaches to no less than 17% of the hindbody length from the ventral sucker. It differs from other species of Stephanostomum with these characteristics by various combinations of the ventral hiatus of the circum-oral spine rows, the relatively long pars prostatica and short ejaculatory duct, the elongate body and the wide gaps between the gonads.